2010
DOI: 10.1186/1471-244x-10-40
|View full text |Cite
|
Sign up to set email alerts
|

Depression and loneliness in Jamaicans with sickle cell disease

Abstract: BackgroundSickle cell disease (SCD) is the commonest genetic disorder in Jamaica, and has life-long implications for those afflicted with it. It is well known that depression and loneliness may exist in those with chronic diseases, but the coexistence of depression and loneliness in people with sickle cell disease is not clear. The aim of this study is to determine the prevalence of and factors associated with depression and loneliness in the Jamaica Sickle Cell Cohort Study and its age and sex matched control… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
52
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(75 citation statements)
references
References 38 publications
11
52
3
Order By: Relevance
“…Poor QOL and depression are often experienced by persons with SCD (Anie, 2005;Asnani, Fraser, Lewis, & Reid, 2010;Edwards et al, 2005). However, the predominant LOC orientation of persons with SCD has not been well studied.…”
Section: Introductionmentioning
confidence: 99%
“…Poor QOL and depression are often experienced by persons with SCD (Anie, 2005;Asnani, Fraser, Lewis, & Reid, 2010;Edwards et al, 2005). However, the predominant LOC orientation of persons with SCD has not been well studied.…”
Section: Introductionmentioning
confidence: 99%
“…In managing serious and unpredictable complications, patients with SCD suffer numerous psychosocial problems such as reduced self-esteem, feelings of frustration (7), depression (7)(8)(9), anxiety and stress (8), and disruption of interpersonal relationships (10); these often lead to fatigue (11)(12)(13)(14) and poor quality of life (13,(15)(16)(17) in these patients. Bakri et al (10) showed that depression, anxiety and stress are prevalent in SC patients compared with healthy subjects.…”
Section: Introductionmentioning
confidence: 99%
“…However, to date, studies investigating this occurrence have frequently produced mixed results with some finding supporting results for this association (Asnani et al, 2010;Hassan, Hashmi, Alhassen, Lawson, & Castro, 2003), while others have not (Laurence, George & Woods 2006;Schaffer et al, 1998).…”
Section: Introductionmentioning
confidence: 93%
“…As a result, the prevalence of a major depressive episode found in individuals suffering from a chronic medical illness varies from as low as 5% to as high as 40% in many instances, and higher in others (Gibson et al, 2013;Sullivan, 1990). Similarly, studies in SCD report the incidence of depressive symptoms ranging from as low as 21.6% to a high of 56.6% (Asnani, Fraser, Lewis, & Reid, 2010;Belgrave & Molock, 1991;Hasan, Hashmi, Alhassen, Lawson, & Castro, 2003;Wison Schaeffer et al, 1999).…”
Section: Introductionmentioning
confidence: 97%